1979
DOI: 10.1111/j.1399-3054.1979.tb01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Levels of Abscisic Acid in Buds and Stems of Acer saccharum

Abstract: Changes in abscisic acid (ABA) were followed in the buds and youngest stems of 6‐year‐old sugar maple (Acer saccharum Marsh.) saplings at approximately monthly intervals during the year. High levels present in the buds in July and August showed a moderate decline through early October, but subsequently increased following leaf fall and reached the maximum values detected during the study in November and December. Thereafter ABA fell sharply, reaching its lowest point immediately prior to budbreak in early May.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 18 publications
2
8
0
3
Order By: Relevance
“…Experiments with ABA show contrasting results. Inhibition of cambium growth through a hypothetical negative interaction with IAA has been suggested (Dumbroff et al , Little and Wareing ), whereas ABA sprayed on maize plants increased phloem and xylem areas in female inflorescences thus enhancing transport of water, nutrients and photoassimilates to grains (Travaglia et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with ABA show contrasting results. Inhibition of cambium growth through a hypothetical negative interaction with IAA has been suggested (Dumbroff et al , Little and Wareing ), whereas ABA sprayed on maize plants increased phloem and xylem areas in female inflorescences thus enhancing transport of water, nutrients and photoassimilates to grains (Travaglia et al ).…”
Section: Introductionmentioning
confidence: 99%
“…(24) observed that ABA levels in buds and stems of A . (24) observed that ABA levels in buds and stems of A .…”
Section: Inhibitormentioning
confidence: 99%
“…Lorsque les explants sont prélevés sur des bourgeons dont la dormance a été levée par un entreposage au froid suffisamment long, les délais de culture sont grandement réduits, diminuant ainsi les coûts de production. Dumbroff et al (1979) rapportent que la concentration d'acide abscissique diminue en fonction de la durée d'entreposage au froid des érables à sucre, atteignant une concentration minimale juste avant le débourrement des bourgeons, ce qui expliquerait la réduction du temps de réactivité des explants en culture in vitro. Dès que la dormance est levée, la vitesse de débourrement des bourgeons est maximale (Kriebel et Wang 1962;Olmsted 1951).…”
Section: Clone* Mise En Culture Multiplicationunclassified